2014
DOI: 10.3390/ijms150814835
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gradual Elongation to the Patella Tendon Insertion in Rabbits

Abstract: The purpose of this study was to examine the histological changes at the patella tendon (PT) insertion site under gradual elongation in rabbits. Gradual elongation of the PT was performed using external fixation for 4 weeks, with a lengthening speed of 0.5 mm/day (elongation group; n = 24). Rabbits in the sham group underwent the same surgical procedure without gradual elongation (sham group; n = 24). Eight animals were sacrificed 1, 2 and 4 weeks after surgery in each group, respectively. Average thicknesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…The chondrocyte apoptosis rate and chondrocyte proliferation rate in the ACL insertion and articular cartilage recovered to the same level as the control group after 8 weeks of remobilization in rabbits that had undergone 2 weeks of immobilization. A previous study reported that the apoptosis of chondrocytes caused by unloading was decreased by reloading in rat bone 18 ) . Furthermore, administration of a drug (salubrinal) reportedly increased the chondrocyte proliferation and reduced the chondrocyte apoptosis under various compressive stresses on the temporomandibular joint in rats 19 ) .…”
Section: Discussionmentioning
confidence: 95%
“…The chondrocyte apoptosis rate and chondrocyte proliferation rate in the ACL insertion and articular cartilage recovered to the same level as the control group after 8 weeks of remobilization in rabbits that had undergone 2 weeks of immobilization. A previous study reported that the apoptosis of chondrocytes caused by unloading was decreased by reloading in rat bone 18 ) . Furthermore, administration of a drug (salubrinal) reportedly increased the chondrocyte proliferation and reduced the chondrocyte apoptosis under various compressive stresses on the temporomandibular joint in rats 19 ) .…”
Section: Discussionmentioning
confidence: 95%
“…This laboratory-based animal study used a judgement sampling technique. Forty-eight male Japanese white rabbits were used because of their history of use for histomorphometric analyses of the ACL insertion and to eliminate the influence of female hormones on the ACL [811, 15]. Because the skeletal growth of rabbits is complete at 6 months [16], we set the evaluation period at 24 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Because this study was an evaluation of the development of fibrocartilage layers in ACL tibial insertions, it could not be considered an in vitro experiment. The animal species to be studied was determined based on previous reports [811]. Moreover, it is considered difficult to prepare tissue specimens using animals smaller than rabbits.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations